Пошаговое объяснение:
Задание №1
1) m²-n²= (m-n)(m+n)
2) a³- 2a= a*(a²-2)
3) b²+2b+1= (b+1)²
4) 9x²+30xy+25y²= (3x+5y)²
Задание №2
1)
2)
3)
4)
5)
6)
7)
Пошаговое объяснение:
Задание №1
1) m²-n²= (m-n)(m+n)
2) a³- 2a= a*(a²-2)
3) b²+2b+1= (b+1)²
4) 9x²+30xy+25y²= (3x+5y)²
Задание №2
1)![\frac{a^{2}-b^{2} }{2a+2b} =\frac{(a-b)(a+b)}{2(a+b)} =\frac{a-b}{2}](/tpl/images/1064/6420/fc0e1.png)
2)![\frac{xy+xz}{y^{2} -z^{2} } =\frac{x(y+z)}{(y-z)(y+z)} =\frac{x}{y-z}](/tpl/images/1064/6420/f3a90.png)
3)![\frac{p^{2} -2p+1}{p^{2}-1 } =\frac{(p-1)^{2} }{(p-1)(p+1)}=\frac{p-1}{p+1}](/tpl/images/1064/6420/41138.png)
4)![\frac{m^{2}-n^{2} }{m^{2}+2mn+n^{2} } =\frac{(m-n)(m+n)}{(m+n)^{2} } =\frac{m-n}{m+n}](/tpl/images/1064/6420/99017.png)
5)![\frac{x-x^{2} }{x^{2}-1 } =\frac{x(1-x)}{(x-1)(x+1)}= -\frac{x}{x+1}](/tpl/images/1064/6420/08c0a.png)
6)![\frac{y^{3}-2y^{2} }{4-y^{2} } =\frac{y^{2}(y-2) }{(2-y)(2+y)} =\frac{-y^{2}(2-y) }{(2-y)(2+y)}=\frac{-y}{2+y}](/tpl/images/1064/6420/41087.png)
7)![\frac{4a^{2}-b^{2} }{4a^{2}+4ab+b^{2} } =\frac{(2a-b)(2a+b)}{(2a+b)^{2} } =\frac{2a-b}{2a+b}](/tpl/images/1064/6420/405b2.png)